Christian barriers to Jesus: conversations and questions from the Indian context - Pennington, J. Paul (William Carey Library, 2017)
The barrier of cultural separatism -- The barrier of Christian -- The barrier of church -- Interlude three foundational barriers -- The barrier of evangelism, gospel, and preaching -- The barrier of conversion -- The barrier of baptism -- The barrier of worship -- The barrier of financial dependency -- The barrier of benevolence -- Final observations -- Hindus and Hinduis